An improved Chase–Pyndiah algorithm in the iterative decoding of turbo product codes. Issue 9 (2nd September 2022) - Yang, Tao; Xi, Zhiyu; Sun, Qifu Tyler
Abstract: This paper considers the design of turbo product codes (TPCs) for short and bursty packages, which is suitable for low latency machine‐to‐machine type communication. A new soft syndrome‐based approach is proposed to compute the weighting factors in the iterative Chase–Pyndiah decoding of TPCs. A new soft syndrome estimation method is developed which has a manageable computational complexity. Numerical results show that the bit error rate performance is improved by using this simple approach for short package sizes for TPCs with high coding rates.